Contestations over Indigenous Participation in Bolivia's Extractive Industry: Ideology, Practices, and Legal Norms - Almut Schilling-Vacaflor (German Institute of Global and Area Studies (GIGA), 2014)
The participatory rights of indigenous peoples have been at the center of conflicts over resource extraction, which have recently increased in number and intensity across Latin America. Using comprehensive empirical data about the Guaraníes' participation in Bolivia's gas sector, this study finds that competing claims regarding territory, property, participation, and decision making provide important explanations for contestations over consultation practices and legal norms in the country. It argues that the main conflicts can be explained by (1) the Bolivian state's focus on directly affected communities and those with formally recognized land titles, something that clashes with the Guaraníes' principle of "territorial integrity"; (2) the state's conviction that it holds a monopoly over subsoil resources, and the limited rights to participation that it is willing to grant as a consequence, which the Guaraníes reject; and (3) the dissonance between state customs and regulations and Guaraní uses and customs.
Keywords: 300; participatory rights; free; prior; and informed consent (FPIC); extractive industry; indigenous peoples; legal pluralism; resource governance; Bolivia